DYNAMICS-AKTION- PEDAGOGICAL DYNAMICS PROPOSAL, USEFUL FOR DESIGN STUDIO TEACHING AND BEYOND. - Besa, Eneko (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This paper is a continuation and a complement to the previous paper: #eindakoa# (what we’ve done) A pedagogical method of Interior Design Projects’ method. That paper developed a pedagogical method of design throughout a full course at a project Design Studio. This paper extends that previous paper and develops its pedagogical approach through a series of pedagogical dynamics and strategies, defined on a more precise and detailed scale. Each dynamic is artistically designed, almost like an action, to create a ‘learning event’ and teach the content of Design Studio through experience. These dynamics are inspiring, to such an extent that they can be transferred to any discipline. However, this article includes a specific theoretical support: a discussion and a comparative contrast with different models of the pedagogical method of the architectural project Design Studio. The first half of the dynamics are developed to enrich a conventional class, prior to the Covid- 19 pandemic. The second half of the dynamics are developed in response to the Covid-19 situation. They creatively exploit the possibilities of different platforms for online teaching.